PENGARUH POLA ASUH ORANGTUA OTORITER TERHADAP EMOSI ANAK USIA DINI DI TK ISLAM BAKTI 77 KENAGARIAN AMPANG KURANJI KECAMATAN KOTO BARU KABUPATEN DHARMASRAYA - sunimaryanti sunimaryanti; Rafqi Amin (Lembaga Penelitian dan Pengabdian Kepada Masyarakat STKIP Ahlussunnah, 2021)
This research originated from the phenomenon of emotional development of children who cannot control their emotions normally when they are angry at school. This study aims to determine the effect of authoritarian parenting on the emotional development of early childhood in TK Islam Bakti 77 Kenagarian Ampang Kuranji Kec. Koto Baru Kab. Dharmasraya. This research is field research using a correlational quantitative approach. The population was the students of class A and B TK Islam Bakti 77. The sample of 40 parents and students were selected by total sampling technique. The instrument used was a questionnaire with a Likert scale. The results showed that there was an effect of authoritarian parenting on emotional development in early childhood.